Effect of a Topical Nonsteroidal Anti-Inflammatory Drug (0.1% Pranoprofen) on VEGF and COX-2 Expression in Primary Pterygium - Yao, Bangtao; Wang, Fei; Zhao, Xiaogui; Wang, Bei; Yue, Xiaoli; Ding, Yuhua; Liu, Gang (Frontiers in Pharmacology, 2021)
Purpose: To evaluate the effect of a topical nonsteroidal anti-inflammatory drug (0.1% pranoprofen) on the expression of VEGF and Cox-2 in primary pterygium. Methods: This was a prospective, randomized study. Between January 2019 and April 2020, 120 patients diagnosed with primary pterygium were enrolled and randomly divided into three groups before operation: (1) 40 patients in group 1 received topical pranoprofen 0.1% four times daily for 4 weeks, (2) 40 patients in group 2 received topical fluorometholone 0.1% four times daily for 4 weeks, and (3) patients in group 3 did not receive treatment. For each group, the age, sex, eye type, best-corrected visual acuity (BCVA), intraocular pressure (IOP), duration of onset, combined systemic diseases, and the results regarding vascular endothelial growth factor (VEGF) and cyclo-oxygen-ase-2 (COX-2) in postoperative pterygial tissues were evaluated in detail. Results: There were no significant differences regarding age, sex, eye type, combined systemic diseases, duration of onset, IOP, and BCVA within the three groups (P>0.05). The  reduction of VEGF and CoX-2 expression of pterygial vascular endothelial cells in group 1 were statistically significant compared to group 2 and group 3 (P<0.05). There were significant correlations between COX-2 and VEGF expression of pterygial tissues within the three groups (P<0.05). Conclusions: The present findings suggested that the topical pranoprofen 0.1% could reduce the expression of VEGF and COX-2 in primary pterygium. We confirmed that treatment with pranoprofen offers advantages in early intervention and has therapeutic potential in reducing the postoperative recurrence of primary pterygium patients.